PERANCANGAN KURSI TANGGA MENGGUNAKAN METODE QUALITY FUNCTION DEPLOYMENT - Sugianto, Antonius; Yuwono, Ngesti; Satriawan, Kristianus (Universitas Tarumanagara, 2020)
Limited space in carrying out activities demanded the availability of furniture that has multifunctional. The purpose of this research is to design a multi-functional Stair Chair. The method used is Quality Function Deployment. The Quality Function Deployment method is used to obtain the product variables desired by most prospective users so that expected design results can fulfill the consumer's wishes. Existing product variables are the description of the main aspects of designing a product i.e. function, shape, construction and material. The main aspects of this design should be considered in order to produce a product design that meets the criteria in designing the correct furniture techniques. The understanding of the importance of ergonomics and anthropometry is indispensable for the main purpose of product design that is appropriate to the wishes of consumers can be fulfilled. Comfort and security become something the parameters must be met. Suitability of the size of furniture with users should be noticed for comfort in use can be fulfilled. Application method of Quality Function Deployment recommends that the development of stair seat products should be aware of the variable needs of consumers who have high weight, namely using strong raw materials, using raw materials that are durable, Using a maximum construction of 2 types, the system of fix assembly. Keywords: design; ladder chair; multi function; quality function deployment ABSTRAKKeterbatasan ruang dalam melaksanakan aktivitas menuntut tersedianya furnitur yang memiliki multifungsi. Tujuan penelitian ini merancang Kursi Tangga yang memiliki multi fungsi. Metode yang digunakan adalah Quality Function Deployment. Metode Quality Function Deployment digunakan untuk mendapatkan variabel produk yang diinginkan oleh sebagian besar calon pemakai sehingga diharapkan hasil perancangan dapat memenuhi keinginan konsumen. Variabel produk yang ada merupakan penjabaran dari aspek utama dalam merancang sebuah produk yaitu fungsi, bentuk, konstruksi dan bahan. Aspek utama dalam perancangan ini harus diperhatikan agar menghasilkan rancangan produk yang memenuhi kriteria dalam teknik mendesain furniture yang benar. Pemahaman akan pentingnya ergonomi dan antropometri sangat diperlukan agar tujuan utama perancangan produk yang sesuai dengan keinginan konsumen dapat terpenuhi. Kenyamanan dan keamanan menjadi sesuatu parameter yang harus dipenuhi. Kesesuaian ukuran furniture dengan pengguna harus diperhatikan agar kenyamanan dalam pemakaian dapat terpenuhi. Aplikasi metode Quality Function Deployment merekomendasikan bahwa pengembangan produk Kursi Tangga harus memperhatikan variabel kebutuhan konsumen yang memiliki bobot tinggi yaitu menggunakan bahan baku yang kuat, menggunakan bahan baku yang awet, menggunakan konstruksi maksimal 2 jenis, sistem perakitan mati.